2013
DOI: 10.4269/ajtmh.2012.12-0359
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Na+/H+ Exchanger (pfnhe-1) Genetic Polymorphism in Indian Ocean Malaria-Endemic Areas

Abstract: Abstract. To date, 11 studies conducted in different countries to test the association between Plasmodium falciparum Na + /H + exchanger gene ( pfnhe-1; PF13_0019) polymorphisms and in vitro susceptibility to quinine have generated conflicting data. In this context and to extend our knowledge of the genetic polymorphism of Pfnhe gene, we have sequenced the ms4760 locus from 595 isolates collected in the Comoros (N = 250; an area with a high prevalence of chloroquine and sulfadoxine-pyrimethamine resistance) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Among the 393 studied sequences, 47 different alleles were observed in samples from Dakar. Consistent with previous reports [22,24,40], Pfnhe-1  ms4760 was highly diverse among parasite isolates. It appears that polymorphisms are more important in Africa and the Indian Ocean region than in India or Asia: in Senegal, 47 different profiles (393 samples) were observed; in the Republic of Congo, 27 different profiles (74 samples) [24]; in Uganda, 40 different profiles (172 samples) [22]; and in the Indian Ocean, 29 different profiles (595 samples) [40], whereas in Vietnam, only ten different profiles (79 samples) were observed [18]; in the China-Myanmar border area, ten different profiles (60 samples) [19]; and…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the 393 studied sequences, 47 different alleles were observed in samples from Dakar. Consistent with previous reports [22,24,40], Pfnhe-1  ms4760 was highly diverse among parasite isolates. It appears that polymorphisms are more important in Africa and the Indian Ocean region than in India or Asia: in Senegal, 47 different profiles (393 samples) were observed; in the Republic of Congo, 27 different profiles (74 samples) [24]; in Uganda, 40 different profiles (172 samples) [22]; and in the Indian Ocean, 29 different profiles (595 samples) [40], whereas in Vietnam, only ten different profiles (79 samples) were observed [18]; in the China-Myanmar border area, ten different profiles (60 samples) [19]; and…”
Section: Discussionsupporting
confidence: 92%
“…This situation likely reflects the level of transmission in these areas and the level of QN selection pressure. The genetic diversity of ms4760, assessed by Nei’s unbiased expected heterozygosity (He), was significantly higher in African isolates (ranged from 0.66 to 0.85) and Indian isolates (0.68) than in Asian isolates (0.49 to 0.68) [40]. Only three profiles (ms4760-1, ms4760-3 and ms4760-7) of the four expected predominant profiles (ms4760-1, ms4760-3, ms4760-6 and ms4760-7) [18-24,40,41] were found to predominate in Senegal.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been found that 78% of all GWAS studies are of European ancestry, with only 2% African representation and 8% East Asian representation [ 28 ]. Only 19 genetic-focused studies have been conducted that included Malagasy populations [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Most of these studies utilize genetic techniques to investigate the genetic lineages of Malagasy populations, whose ancestral history has been widely disputed.…”
Section: Introductionmentioning
confidence: 99%
“…trinucleotide or hexanucleotide repeats) will not result in a frame-shift mutation when repeats are deleted or added, but can change protein sequences [10]. For example, the Pfnhe-1 protein contains a polymorphic amino acid motif DNNND (GATAACAATAATGAT) and DDNHNDNHNND (GATGATAACCATAATGATAATCATAATAATGAT) which affects the P. falciparum Na+/H+ exchanger capabilities, and influences quinine resistance by combining Pfcrt and Pfmdr1 [11,12].…”
Section: Introductionmentioning
confidence: 99%